New Insights and Emerging Therapeutic Approaches in Prostate Cancer - Licitra, Fabrizio; Giovannelli, Pia; Di Donato, Marzia; Monaco, Alessandra; Galasso, Giovanni; Migliaccio, Antimo; Castoria, Gabriella (Frontiers in Endocrinology, 2022)
Prostate cancer is the second most frequently diagnosed cancer in men and several therapeutic approaches are currently available for patient’s care. Although the androgen receptor status represents a good predictor of response to androgen deprivation therapy, prostate cancer frequently becomes resistant to this approach and spreads. The molecular mechanisms that contribute to progression and drug-resistance of this cancer remain still debated. At this stage, however, few therapeutic options are available for patient’s management. Recent years have seen a great expansion of the studies concerning the role of stromal-epithelial interactions and tumour microenvironment in prostate cancer progression. The findings so far collected have provided new insights into diagnostic and clinical management of prostate cancer patients. Further, new fascinating aspects concerning the intersection of the androgen receptor with survival factors as well as calcium channels have been reported in cultured prostate cancer cells and mouse models. The results of these researches have opened the way for a better understanding of the basic mechanisms involved in prostate cancer invasion and drug-resistance. They have also significantly expanded the list of new biomarkers and druggable targets in prostate cancer. The primary aim of this manuscript is to provide an update of these issues, together with their translational aspects. Exploiting the power of novel promising therapeutics would increase the success rate in the diagnostic path and clinical management of patients with advanced disease.